The Value of Unconscious Human Behavior in Product Design Innovation - Muhammad Jameel, Mohamed Kamil; Shahriman, Zainal Abidin (2014)
This paper evaluates a new perimeter of design thinking with respect to the value of unconscious human behavior, as well as the direction for the development of innovative product design. The paper reviews the literature on the value of unconscious human behavior in the design perspective. Freud’s theory of mind and Bargh’s model of the unconscious behavioral guidance system are being reviewed. Furthermore, four attributions of unconscious everyday human behaviors, which contribute in design concepts and ideation, are also being explored along with the model of obvious needs and latent needs in everyday life, which educate a designer about how unconscious human behavior could indicate user’s implicit needs